Katekese Literer di Era Digital dan Tantangan Budaya Instan terhadap Kedalaman Iman - Patrisia Rera Bato; Monica Innanda Chiaralazzo; Intansakti Pius X (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
The rapid development of digital technology has transformed patterns of communication, learning processes, and the ways believers access religious information in daily life. While this transformation provides easier access to information, it also fosters an instant culture characterized by fast, brief, and less reflective information consumption. This condition poses significant challenges for the Church, particularly in faith formation, as it may weaken the depth of believers’ understanding of faith. This study aims to examine the role of literate catechesis as a response to the instant culture of the digital era, while also exploring the opportunities offered by digital media in faith proclamation. This research employs a qualitative approach using a literature review method based on relevant academic sources. The findings indicate that literate catechesis plays a crucial role in fostering mature faith through reading, reflection, and critical thinking processes, enabling believers not only to consume information but also to internalize and live out their faith more deeply. On the other hand, digital media offers significant opportunities to develop catechesis that is broader, more participatory, and contextually relevant. Integrating reflective depth with creative digital approaches is essential to ensure that faith formation remains both meaningful and relevant within an increasingly instant-oriented culture.